Enteric Fever in Children in Western Sydney, Australia, 2003–2015. Issue 12 (December 2017) - Khatami, Ameneh; Khan, Fouzia; Macartney, Kristine K.
Abstract : Background: Enteric fever is a vaccine-preventable disease with cases in Australia predominantly acquired overseas. The aim of this study was to define the burden of enteric fever in children presenting to a pediatric hospital in Western Sydney between 2003 and 2015. Methods: Cases between January 2003 and December 2013 were ascertained through medical records using International Classification of Disease–coded discharge diagnoses, cross-referenced with microbiology laboratory data for all isolates of Salmonella enterica serovar typhi and S. enterica serovar paratyphi. Prospective cases from January 2014 to April 2015 were additionally captured through records maintained by the infectious diseases team. Results: Seventy-one cases of enteric fever were identified in 12.3 years with an average of 4 cases per year between 2003 and 2008 and 7 cases per year between 2009 and 2014. Two were visitors to Australia, 8 were recent migrants, and 59 were Australian residents returning from overseas travel. Two children had no history of overseas travel. Countries of travel predominantly included the Indian subcontinent (60/69) and Southeast Asia (7/69). Of 30 children with information available on pretravel medical consultation, 1 was offered and received typhoid vaccine. Ninety-four percent of children (67) required admission for 1–28 days (median: 5 days). Three children required readmission, with 1 case of presumed relapse. Ninety percent (64) were diagnosed by blood or stool culture with S. enterica serovar typhi the predominant organism (54/64). Conclusions: In Australia, hospitalizations for pediatric enteric fever appear to be increasing; predominantly occurring in Australian-resident children. Greater awareness and education are required for parents and clinicians regarding travel health risks and prevention strategies. Abstract : Supplemental Digital Content is available in the text.